Characteristics of farmers' selection criteria for cowpea (Vigna unguiculata) varieties differ between north and south regions of Burkina Faso. (18th February 2020) - Ishikawa, Haruki; Drabo, Issa; Joseph, Batieno B.; Muranaka, Satoru; Fatokun, Christian; Boukar, Ousmane
Summary: Comparative analysis of preferences and key criteria for selecting cowpea ( Vigna unguiculata L. Walp.) varieties was conducted using the data collected from farmers' participatory varietal selection (FPVS) activities conducted over 3 years with a total of 2401 farmers (1230 male and 1171 female) in 13 villages in Tougouri department in northern region and Tiéfora department in southern region of Burkina Faso in West Africa. Over the 3 years, farmer criteria for variety selection remained basically stable, but some variations among the regions and years were noticed. Grain yield was the most common and the most important criterion for farmers' choice in both regions. Farmers in Tougouri (north) put more emphasis on early maturity (90%) and drought resistance (19.7%) as selection criteria than farmers in Tiéfora (south). Farmers in Tiéfora placed statistically significant importance on seed colour and plant type, while farmers in Tougouri did not, and for these selection criteria, there were only slight differences between genders in both areas. Results of stepwise multiple regression indicated that maturity and seed colour in the north, and seed size and seed colour in the south were the most important selection factors for farmers to select cowpea varieties. Improved varieties should have sufficiently good yield to be accepted, but other favoured traits may differ by target region as a reflection of local and regional market demands as well as deep-rooted cultural preferences. Understanding local and regional differences in selection criteria for cowpea varieties is necessary to improve the acceptance of newly released improved varieties. Preferences identified in the participatory activities could inform further development of cowpea breeding strategies for north and south regions of Burkina Faso.